Band‐tailored van der Waals heterostructure for multilevel memory and artificial synapse. Issue 8 (13th July 2021) - Wang, Yanan; Zheng, Yue; Gao, Jing; Jin, Tengyu; Li, Enlong; Lian, Xu; Pan, Xuan; Han, Cheng; Chen, Huipeng; Chen, Wei
Abstract: Two‐dimensional (2D) van der Waals heterostructure (vdWH)‐based floating gate devices show great potential for next‐generation nonvolatile and multilevel data storage memory. However, high program voltage induced substantial energy consumption, which is one of the primary concerns, hinders their applications in low‐energy‐consumption artificial synapses for neuromorphic computing. In this study, we demonstrate a three‐terminal floating gate device based on the vdWH of tin disulfide (SnS2 ), hexagonal boron nitride (h‐BN), and few‐layer graphene. The large electron affinity of SnS2 facilitates a significant reduction in the program voltage of the device by lowering the hole‐injection barrier across h‐BN. Our floating gate device, as a nonvolatile multilevel electronic memory, exhibits large on/off current ratio (~10 5 ), good retention (over 10 4  s), and robust endurance (over 1000 cycles). Moreover, it can function as an artificial synapse to emulate basic synaptic functions. Further, low energy consumption down to ~7 picojoule (pJ) can be achieved owing to the small program voltage. High linearity (<1) and conductance ratio (~80) in long‐term potentiation and depression (LTP/LTD) further contribute to the high pattern recognition accuracy (~90%) in artificial neural network simulation. The proposed device with attentive band engineering can promote the future development of energy‐efficient memory and neuromorphic devices. Abstract : A three‐terminal floating gate device consisted of tin disulfide (SnS2 ), hexagonal boron nitride (h‐BN), and few‐layer graphene is demonstrated based on the attentive band engineering. It can function as a nonvolatile multilevel electronic memory featuring the excellent characteristics. For the emulation of artificial synapse, multiple synaptic functions can be realized with the low energy consumption.